Interest In Reading Students of Class V 161 Pekanbaru State Elementary School - Siti Irva Gustina; Febrina Dafit (Budapest International Research and Critics University, 2022)
This study aims to describe the students' reading interest and the factors that influence the fifth grade students' reading interest at the State Elementary School 161 Pekanbaru. This type of research is descriptive qualitative research. The data sources in this study were one homeroom teacher and six fifth grade students. Data collection techniques in this study used interview, observation, and documentation techniques. Data analysis used the Milles and Huberman model with three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the reading interest of fifth grade students at the State Elementary School 161 Pekanbaru was still low. This is because students' attention to reading activities at school is still lacking. Then awareness of the importance of reading and the benefits of reading is still lacking. Based on the research, there are factors that influence the reading interest of fifth grade students, namely intellectual factors, family environmental factors and psychological factors. Results Based on the research, the reading interest of fifth graders at State Elementary School 161 Pekanbaru is still not good. This is caused by factors that arise from the students themselves.